Caracterização da cadeia produtiva de peixes ornamentais de águas continentais nos estados do Ceará e Pernambuco - Freitas, Marcelo Carneiro de (2012)
This study aimed at evaluating the productive chain of freshwater ornamental fish of northeastern Brazil. The study was conducted in the states of Ceara and Pernambuco, to be recognized exporters of these bodies in the country.Data for the study were obtained through questionnaires representatives in retail, ornamental fish-farming and hobbysts. Production data on domestic trade and export of ornamental fish were obtained in public institutions. A total of 18 ornamental fish hatcheries were visited, 10 in Ceará and 8 in Pernambuco, ranging from small to large fish-farming.The species of fish sold by the fish farmers were Carassius auratus, Pterophyllum scalare, Betta splendens, Poecilia latipina and Xiphophorus helleri. The production was designed primarily for state of Rio de Janeiro and São Paulo. Retail trade of ornamental fish in the northeast is diverse and can find their products for sale in petshops and specialty stores. A total of 13,846 specimens of freshwater ornamental fish were visualized by visual census in the shops of Ceara and Pernambuco. A total of 35 families and 194 species of fish have been identified, greater participation in number of individuals were from families Cyprinidae, Characidae and Poeciliidae. The most representative species in number of individuals available for sale in retail trade were: Carassius auratus, Poecilia latipina, Paracheirodon axelrodi, Brachydanio rerio e Pterophyllum scalare. In domestic trade, the state of Ceara sold in the biennium 2006/2007, a total of 373,085 specimens of ornamental fish, corresponding a total value R$ 250,565.03, while Pernambuco sold in 2010, a total of 916,240 individuals, corresponding R$ 1,198,094.67.The total production of ornamental fish exported by the states of Ceara and Pernambuco in the period 2006 to 2008 was R$ 377,584.91, with higher volume related to Pernambuco corresponding R$ 211,175.27. The main export destinations were Japan, Germany, UK, Hong Kong and Netherlands. A total of 102 species was exported, the most representative in number of individuals were Paracheirodon axelrodi, Parotocinclus maculicauda, Baryancistrus sp. e Ancistrus spp. The Brazilian Northeast has a great potential for the activity of freshwater ornamental fish, being a source of labor and income for the populations of rural and urban areas. But several points need to be corrected so that this activity is sustainable and that those involved can enjoy for a long time their products.